2010
DOI: 10.3390/rs2040908
|View full text |Cite
|
Sign up to set email alerts
|

Using Spatial Structure Analysis of Hyperspectral Imaging Data and Fourier Transformed Infrared Analysis to Determine Bioactivity of Surface Pesticide Treatment

Abstract: Many food products are subjected to quality control analyses for detection of surface residue/contaminants, and there is a trend of requiring more and more documentation and reporting by farmers regarding their use of pesticides. Recent outbreaks of food borne illnesses have been a major contributor to this trend. With a growing need for food safety measures and -smart applications‖ of insecticides, it is important to develop methods for rapid and accurate assessments of surface residues on food and feed items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…Compared with classical taxonomy (under the microscope) or molecular-based classification of minute and closely related animals, plant seeds and growing plants, a reflectance-based method may be of considerable relevance to a wide range of biological studies. There are numerous approaches to classification of hyperspectral imaging data, and only recently has the approach (a combination of variogram analysis and linear discriminant analysis) used in this study been described and successfully applied (Nansen, 2012;Nansen et al, 2010a;Nansen et al, 2009;Nansen et al, 2014). However, this analysis represents the first application of this classification method to the identification of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with classical taxonomy (under the microscope) or molecular-based classification of minute and closely related animals, plant seeds and growing plants, a reflectance-based method may be of considerable relevance to a wide range of biological studies. There are numerous approaches to classification of hyperspectral imaging data, and only recently has the approach (a combination of variogram analysis and linear discriminant analysis) used in this study been described and successfully applied (Nansen, 2012;Nansen et al, 2010a;Nansen et al, 2009;Nansen et al, 2014). However, this analysis represents the first application of this classification method to the identification of animals.…”
Section: Discussionmentioning
confidence: 99%
“…This low spider mite infestation level was intentional, as the objective was to test variogram based analysis on a challenging model system, and variogram parameters did respond significantly despite the fact that analysis of average reflectance values in the same spectral bands yielded no consistent trends. A recent study involving experimental manipulation of reflectance data (adding 2.5% or 5.0% to reflectance values in all or random subsets of pixels) showed that increase in reflectance especially affected sill values and to some extent also effected nugget values but had negligible effect on range values [24]. Thus, if mainly sill values respond to increases in reflectance values, it is not surprising that this study showed negligible increase in average reflectance and non-consistent response by sill values to the 2 stressors.…”
Section: Dual Stress Detectionmentioning
confidence: 99%
“…Similar to methodology used in previously published studies (Nansen et al, 2010a;Nansen et al, 2010b), we used a hyperspectral spectral camera (PIKA II, Resonon Inc., Bozeman, MT) mounted 40 cm above target objects (field peas). The main specifications of the spectral camera are as follows: interface, Firewire (IEEE 1394b); output, digital (12 bit); 240 bands from 392 to 889 nm (spectral resolution = 2.1 nm) (spectral) by 640 pixels (spatial); angular field of view of 7°.…”
Section: Hyperspectral Imaging Datamentioning
confidence: 99%
“…Spatial structure analysis based on geostatistics (variogram analysis) is considered one of the most powerful and robust approaches to spatial data analysis (Isaaks and Srivastava, 1989), and recent studies have shown how variogram parameters derived from high-resolution reflectance data can be used to detect different traits in a range of target objects (Nansen, 2011(Nansen, , 2012Nansen et al, 2010a;Nansen et al, 2010b;Nansen et al, 2009;Nansen et al, 2010c). In the variogram analysis (PROC VARIOGRAM) of reflectance data at 782 nm, we used the following variogram settings: (1) lag distances = 1, and (2) number of lag intervals = 10.…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 1 more Smart Citation